Biological and Immunomodulator Use in Crohn's Disease in a Medicaid Population. Issue 5 (25th February 2016) - Flasar, Mark H.; Chao, Jingdong; Ozbay, A. Burak; Skup, Martha; Lu, Mei; Cross, Raymond
Abstract: Background: Immunomodulator and biological use in African Americans (AA) with Crohn's disease (CD) has been reported to be lower than in whites (W); less data exist for Hispanics (H). Methods: Medicaid databases from 3 states were examined for patients with CD from August 1998 to July 2009. CD-related treatments, comorbidities, location, surgery, and health care utilization were assessed from diagnosis until the first biological claim or end of claims. A Cox proportional hazard regression model was used to assess the effect of race on biological initiation. Results: A total of 5575 patients with CD (3590 W; 924 AA; 494 H; and 567 "other") were analyzed; 18%, 17%, and 17% of W, AA, and H patients, respectively, started immunomodulators ( P = not significant); and 7%, 9%, and 5% of W, AA, and H, respectively, initiated biologics after CD diagnosis ( P = not significant). After adjusting for demographics and CD-related medications and comorbidities in Cox models, no association was found between AA and W for biological use (hazard ratio 1.19; 95% confidence interval [CI], 0.91–1.54) or H and W (hazard ratio 0.68, 95% CI, 0.45–1.02). Analyzing patients hospitalized after CD diagnosis (n = 3428) to adjust for disease severity demonstrated that H were significantly less likely to use biologics than W (hazard ratio 0.40, 95% CI, 0.22–0.74). No differences between W and AA were found. Conclusions: Our findings suggest that differences between AA and W in exposure to immunomodulators or biologics may not exist, although they may be present in H with more severe disease. Further research is needed to confirm these findings.